2016
DOI: 10.1093/geronb/gbw043
|View full text |Cite
|
Sign up to set email alerts
|

Midlife Work-Related Stress Increases Dementia Risk in Later Life: The CAIDE 30-Year Study

Abstract: Midlife work-related stress increases the risk for MCI, dementia, and Alzheimer's disease in later life. The association was not seen after the extended follow-up possibly reflecting selective survival/participation, heterogeneity in dementia among the oldest old, and a critical time window for the effects of midlife stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 48 publications
5
63
1
3
Order By: Relevance
“…A time window of midlife working stress affects dementia onset has been reported . We found that any high job strain experienced before age 40 increased the risk of T2DM, not after the age of 40.…”
Section: Discussionsupporting
confidence: 46%
“…A time window of midlife working stress affects dementia onset has been reported . We found that any high job strain experienced before age 40 increased the risk of T2DM, not after the age of 40.…”
Section: Discussionsupporting
confidence: 46%
“…An initial study found that higher work-related stress, as indicated by low job control and high job demands, was associated with a higher risk of late-life dementia [60]. However, support for this finding has been mixed in subsequent research [61,62]. …”
Section: Psychosocial Factors and Cognitionmentioning
confidence: 99%
“…Environmental and life-style factors such as stress 5 , diet 6 and physical activity were shown to affect cognition 7 and could also affect the risk of LOAD. Evidence suggests that high fat/high cholesterol diet (HFD) could modify the risk for LOAD.…”
Section: Introductionmentioning
confidence: 99%